Combined effects of heavy metals and microplastics on maize grown in acid and alkaline soils inoculated with plant growth promoting rhizobacteria - Asma Shabani; Reza Ghasemi-Fasaei; Mehdi Zarei; Sajjad Abbasi (PLoS ONE, 2025)
Microplastic particles (MPs) are recognized as novel pollutants, and their interactions with heavy metals (HMs) in soil can threaten ecosystem health and agricultural productivity. This study evaluates the combined effects of biodegradable polylactic acid (PLA) and non-biodegradable low-density polyethylene (LDPE) MPs and HMs include lead (Pb), cadmium (Cd), zinc (Zn), and nickel (Ni) on soil properties and maize growth. Maize was grown in alkaline (pH = 7.8) and acidic (pH = 5.6) soils under five MPs treatments (control, 1% LDPE, 5% LDPE, 1% PLA and 5% PLA) and Plant growth-promoting Rhizobacteria (PGPR) treatments including control, Pseudomonas fluorescens ( P. fluorescens ) and Azospirillum lipoferum ( A. lipoferum ) for 50 days. Results showed that PLA increased soil pH, while LDPE decreased it. Microplastic particles elevated electrical conductivity (EC) and dissolved organic carbon (DOC), with LDPE having a stronger effect on EC and PLA on DOC. LDPE enhanced HMs uptake in maize, whereas PLA decreased it. In alkaline soil, both MPs reduced plant biomass; however, reduction was not significant in PLA treatments. In contrast, in acidic soil, PLA increased shoot and root dry weights by 22.5% and 47.95%, respectively. The 5% LDPE treatment without bacteria caused the most significant reduction in shoot and root dry weights with decreases of 33.4% and 42.8% in alkaline soil; 26.8% and 21.1% in acidic soil respectively. PGPR increased soil DOC, improved plant growth, mitigated LDPE’s negative effects, and amplified PLA’s benefits. These findings highlight the importance of MP type, soil conditions, and PGPR for managing MPs-HMs contamination, with PLA and PGPR as sustainable agriculture strategies.